2009
DOI: 10.4103/0972-9941.59306
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cholelithiasis and laparoscopic management: A review of twenty two cases

Abstract: AIM:To evaluate the role of laparoscopic cholecystectomy (LC) in the management of cholelithiasis in children.MATERIALS AND METHODS:A retrospective review of our experience with LC for cholelithiasis at our institution, between April 2006 and March 2009 was done. Data points reviewed included patient demographics, clinical history, haematological investigations, imaging studies, operative techniques, postoperative complications, postoperative recovery and final histopathological diagnosis.RESULTS:During the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…It is consistent with similarly situated studies in the literature. 5,6,19,20 The male: female ratio in our study was 1.85: 1 (52 vs 28). Strausse et al in his study observed females dominance i.e.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…It is consistent with similarly situated studies in the literature. 5,6,19,20 The male: female ratio in our study was 1.85: 1 (52 vs 28). Strausse et al in his study observed females dominance i.e.…”
Section: Discussionmentioning
confidence: 55%
“…9 Similarly, Deepak J et al observed that 20 patients had pigmented stones and 02 patients had cholesterol stones. 6 Mean operative time in present study was 26.92 minutes (15 to 50 minutes). This was much less than OT reported by other available studies in the literature.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations